Local texture description framework-based modified local directional number pattern: a new descriptor for face recognition. (2015) - Rose, R. Reena; Suruliandi, A.; Meena, K.
Texture descriptors effectively capture the surface property of images. However, almost all the available local texture descriptors encode a texture pattern using the closest neighbours. But the local texture description framework (LTDF) proposed earlier proved the importance of eight sampling points that lie elliptically at a certain distance apart from a pixel under consideration in distinguishing different face images. Recently, a local texture descriptor namely local directional number pattern (LDN) is introduced to encode the directional information of the structure of a face's texture. Incorporating the concepts of LTDF and LDN, this paper proposes a new texture descriptor namely LTDF-based modified local directional number pattern (LTDF_MLDN). LTDF_MLDN describes a texture pattern with the sampling points at dissimilar area. Effectiveness of the system is tested for the different issues in face recognition using five benchmark databases. Experimental results reveal the effectiveness of the proposed descriptor over the state-of-the-art approaches.